AN ANALYSIS OF THE IMPACT OF FINANCIAL LITERACY ON HOUSEHOLD WEALTH ACCUMULATION: A STUDY BASED ON DEMOGRAPHIC DATA OF SELECTED RESIDENTS IN UTTAR PRADESH. - Raghvendra; Saxena, Tulika (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This paper examines the impact of financial literacy on household wealth accumulation, focusing on selected residents of Uttar Pradesh. Utilizing secondary demographic data, the study analyzes the relationship between financial literacy levels and wealth-building behaviors across various demographic groups. Statistical methods are employed to examine how financial literacy influences household wealth, revealing significant positive correlations. The findings highlight the essential role of financial literacy in fostering economic well-being and suggest that integrating financial education into broader programs can lead to sustained wealth accumulation in the region.